Stochastic Resonance Reduces Sway and Gait Variability in Individuals With Unilateral Transtibial Amputation: A Pilot Study - Likens, Aaron D.; Kent, Jenny A.; Sloan, C. Ian; Wurdeman, Shane R.; Stergiou, Nick (Frontiers in Physiology, 2020)
Subthreshold (imperceptible) vibration, applied to parts of the body, impacts how people move and perceive our world. Could this idea help someone who has lost part of their limb? Sub-threshold vibration was applied to the thigh of the affected limb of twenty people with unilateral transtibial amputation. Vibration conditions tested included two noise structures; pink and white. Center of pressure (COP) excursion (range and root mean-square displacements) during quiet standing; and speed and spatial stride measures (mean and standard deviations of step length and width) during walking were assessed. Pink noise vibration decreased COP displacements in standing, and white noise vibration decreased sound limb step length standard deviation in walking. Subthreshold vibration positively impacted aspects of both posture and gait, however different noise structures had different effects. The current study represents foundational work in understanding the potential benefits of incorporating stochastic resonance as an intervention for individuals with amputation.